Analysis of The Effectiveness of the Implementation of Education and Training (Case Study of Training in the Management of Regional Property within the Government of West Nusa Tenggara) - Kuntary Ibrahim, Isra Dewi; Kurniawati; Cahyadi, Irwan (Westscience Press, 2025)
The purpose of this study was to determine the level of effectiveness of the 2022 West Nusa Tenggara Government Regional Asset Management training program which has been implemented by the West Nusa Tenggara Province Regional Human Resources Development Agency. This study uses a descriptive qualitative method through a case study approach with interview data collection techniques obtained directly from respondents. The results of this study are that the education and training program implemented by the NTB Province Regional Human Resources Development Agency has been effective as seen from the effectiveness analysis through five levels, but from the five levels, further training is still needed for participants in managing goods to better understand the use of technology or applications used.